UCC 사용자 참여수준과 개인적 및 문화적 특성 요인과의 관계 - 한국과 미국을 중심으로 - 이현주; 김유정; 강소라; Lee, Hyun-Ju; Kim, Yoo-Jung; Kang, So-Ra (한국콘텐츠학회 논문지, 9(2), 2009)
The purpose of this paper is to examine the ethical implications in UCC participation. This paper aimed at examining the advent of UCC as a critical media tool in interactive two-way communication and the effect of ethical questions on the level of UCC participation. The findings show that uncertainty avoidance gives an positive and significant effect on privacy concern and regulatory preference, but it is not related to copyright invasion in Korea and U.S.A. It is shown that privacy concern does not influence on UCC retrieval in Korea whereas it is positively related to UCC retrieval in the United States. Also, privacy concern has not relationship with UCC production(modification, recreation, generation) in both nations. In the case of regulatory preference, it posits an significant and positive effect on UCC retrieval in Korea while it is not related to UCC retrieval in the United States. Also, regulatory preference does not affect on UCC production in Korea whereas it influences on UCC generation without impacting UCC modification and recreation in U.S.A. Finally, the results show that copyright invasion has stronger relationship with UCC recreation and generation than UCC modification, and it is positively related to UCC retrieval in both nations. 본 연구의 목적은 UCC 참여활동에 있어서의 윤리적 함의를 검토하고자 하였다. UCC 참여활동에 프라이버시 우려도, 규제에 대한 선호도 및 저작권 침해가 어떠한 영향을 미치는가를 UCC 조회, 수정, 재생산 및 창작수준별로 파악하고자 하였다. 연구결과, 한국과 미국 모두에서 불확실 회피성향은 프라이버시 우려도와 규제에 대한 선호도에 유의미한 수준에서 긍정적인 영향을 미치는 것으로 나타났으나, 저작권 침해와는 관련성이 없는 것으로 나타났다. 프라이버시 우려도은 한국의 경우 UCC 조회와는 관련성이 없는 것으로 나타났으나, 미국에서는 프라이버시 우려도가 UCC 조회에 긍정적인 영향을 미치는 것으로 나타났다. 한국과 미국 모두에서 프라이버시 우려도와 UCC 생산과는 관련성이 없는 것으로 밝혀졌다. 규제에 대한 선호도는 한국의 경우 UCC 조회에 긍정적인 영향을 미치고 있으나, 미국에서는 규제에 대한 선호도와 UCC 조회간의 관련성이 없는 것으로 밝혀졌다. 한국에서는 규제에 대한 선호도가 UCC 수정, 재생산 및 창작과 관련성이 없으며, 미국의 경우 규제에 대한 선호도가 수정 및 재생산에는 영향을 미치지 않지만, UCC 창작수준에는 부정적인 영향을 미치는 것으로 나타났다. 마지막으로 한국과 미국에서 저작권 침해가 UCC 조회에 긍정적인 영향을 주었으며, UCC 수정보다는 재생산과 창작에 더 많은 영향을 미치는 것으로 밝혀졌다.